Effect of Sandblasting on Retention of Maxillary Complete Denture - Mohammad Ali Hemmati; Ali Jamali; Sakineh Barzegar; Farnoosh Taghavi (Islamic Dental Association of Iran, 2015)
Background and Aim: Retention of complete denture plays an important role in patient satisfaction. The aim of this study was to evaluate the effect of sandblasting of the internal surface of maxillary denture on its retention. Materials and Methods: In this before and after clinical trial, for 15 patients presenting to the Department of Prosthodontics of Shahed University, two acrylic bases similar to their original maxillary denture were fabricated. By using a digital force transducer, the force needed to dislodge the base from the palate was measured. The internal surface of the bases was sandblasted by 50-micron alumina particles for one minute except for the borders, which were covered by thin aluminum foils. The data were analyzed using paired t-test. Results: Sandblasting increased the mean retention of the bases from 30.89±10.74 N to 37.66±9.76 N (21.9%), which was statistically significant (p<0/0001). Conclsion: According to the findings of the present study, sandblasting of the internal surface of maxillary complete denture enhances its retention.